Pore Pressure Response to Groundwater Fluctuations in Saturated Double-Layered Soil. (1st June 2015) - Ying, Hongwei; Zhang, Lisha; Xie, Kanghe; Huang, Dazhong
Abstract : Analytical solutions are developed for one-dimensional consolidation of double-layered saturated soil subjected to groundwater fluctuations. The solutions are derived by an explicit mathematical procedure using Duhamel's theorem in conjunction with a Fourier series, when groundwater fluctuation is described by a general time-dependent function and assumed to be the pore water pressure variations at the upper boundary. Taking as an example the harmonic groundwater fluctuation, the relevant response of the excess pore water pressure is discussed in detail, and the main influencing factors of the excess pore pressure distribution are analyzed. A dimensionless parameter θ has been introduced because it significantly affects the phase and the amplitude of excess pore pressures. The influences of the coefficients of permeability and compressibility of soil on the excess pore pressure distribution are different and cannot be incorporated into the coefficient of consolidation in double-layered soil. The relative permeability ratio of two clayey soils also plays an important role on the curves of the distributions of the excess pore pressures. The effects of the thickness of the soil layer on the excess pore pressure distribution should be considered together with the dimensionless parameter θ and the permeability and compressibility of the double-layered soil system.